THE ROLE OF DIGITAL ASSET INVESTMENT IN COUNTRY ECONOMIC GROWTH - Reza Juanda; Falahuddin; Muttaqien; Rico Nur Ilham; Frengki Putra Ramansyah; Muhammad Multazam (PT. Radja Intercontinental Publishing, 2024)
Cryptocurrency is one of the investment commodities that can generate returns and already has a permit to be traded in exchange trading through the Indonesian Commodity Futures Trading Supervisory Agency (BAPEPTI). Digital crypto assets traded in Indonesia are quite a lot through the Indodax trading company. The purpose of this study is focused on formulating a risk management process in investing in digital cryptocurrency assets. In addition, the results of this study will produce policy recommendations known as LCTR or